Development Of Students' Creative Skills in Solving Some Algebraic Problems Using Surface Formulas of Geometric Shapes - O.U.Pulatov; M.M.Djumayev (Genius Journals, 2022)
This article discusses some aspects of developing students’ creative activity in solving some of the problems in the Planimetry course, and provides specific examples of how each method studied can be used in teaching geometry
Keywords: Triangle median; altitude; system; surface